The Role of Classroom Input: Processing Instruction, Traditional Instruction, and Implicit Instruction in the Acquisition of the English Simple Past by Cantonese ESL Learners in Hong Kong. (February 2019) - Chan, Mable
Abstract: The purpose of this study was to examine the role of classroom input in achieving the English simple past to unite the insights of SLA theory and L2 pedagogy. As English tense is not realized overtly in Cantonese, it has been causing great difficulty to English as a Second Language (ESL) learners. This study involved Primary 2 students who were divided randomly into 3 groups being taught using 3 different forms of classroom intervention: Processing Instruction Group (PI), Traditional Instruction Group (TI), and Implicit Instruction Group (II). A pre-test and a post-test consisting of interpretation and production tasks were administered to examine if there is any significant difference in the performance after classroom intervention. Findings show that the PI group displayed significant improvement from pre-test to post-test in the interpretation task, and they also obtained the greatest gains. In the production task, both PI and TI groups obtained greatest gains. Pedagogical implications are discussed suggesting what teachers can do to help L2 learners map forms and meaning in acquiring English tense and other relevant grammar items in the initial stages of L2 acquisition.